Deficient Emotional Self-Regulation in ADHD Assessed Using a Unique Profile of the Child Behavior Checklist (CBCL): Replication in an Italian Study. (October 2015) - Donfrancesco, R.; Innocenzi, M.; Marano, A.; Biederman, J.
Objective: A unique profile of the empirically derived Child Behavior Checklist–anxious/depressed, attention, and aggression–deficient emotional self-regulation (CBCL-AAA-DESR profile: ≥180 and ≤210) may be used to identify a sizable minority of children with ADHD with associated DESR. The main aim of this study was to replicate these findings in an Italian sample.Method: The sample consisted of 358 children and teenagers aged 6 to 17 years of both sexes with ( n = 190) and without a diagnosis of ADHD ( n = 168).Results: In all, 40.0% of children with ADHD had a positive CBCL-DESR profile compared with 3.5% of controls. Receiver-operating characteristic analysis showed that the CBCL-DESR profile cut-off (sensitivity = 97.33, specificity = 79.66, criterion ≥179, ≤210) discriminated the two subsamples.Conclusion: The findings replicate previous results highlighting the utility of the CBCL as a means of identifying DESR in children with ADHD.